# Thread: [We hope that you choke]

1. ## [We hope that you choke]

1: Take the equation a = b

2: Now multiply both side of the equation by a, giving:
a2 = ab

3: Add a2 - 2ab to each side, which gives:
a2 + a2 - 2ab = ab + a2 - 2ab

4: Simplify that equation:
2(a2 - ab) = a2 -ab

5: Divide both sides by (a2 - ab), which, astonishingly gives:

2 = 1

2. (You cannot divide by (a2 - ab), since (a2 - ab) may be zero).

3. The reason that works is because a2 = ab, hence a2 - ab = 0.

EDIT: blast shiro beat me to it =)

4. hehehe

5. >> The reason that works is because a2 = ab, hence a2 - ab = 0.

That is just the perfectly logical solution. how come i didn't see that?!?! I must sharpen my math skills.

6. >>Now multiply both side of the equation by a, giving:
>>a2 = ab

a * a = a to the power of 2 ( i dunno fi this affects the outcome, though...

or did a2 mean a to the power of 2?

7. wait! there is still a problem.
if a2-ab is 0, then we are dividing both sides by 0.
dividing anynumber by 0 is infinity or in other words undefined.

so how can there be 2(infinity)?? that is still infinity.
infinity=a number bigger than the biggest number.
if there is 2(infinity), that is the biggest number, hence infinity.
so is infinity=2(infinity)
so, multiplying infinity by any number gives you infinity? that is the same type of property zero has. so is infinity similar ro zero? is infinity=0???

ohhh this is soooooo confusing...
*\ getting dizzy. brain fries. faints /*

8. a * a = a to the power of 2 ( i dunno fi this affects the outcome, though...

or did a2 mean a to the power of 2?
a2 means a to the power of 2.in other words, a^2. which is the same as "a squared".